Tracing the Chiasmus: A Response to William Renwick - Krims, Adam (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2000)
This response addresses those of Renwick's critiques that can be addressed briefly: the status of a Schenker analysis not done by Schenker, whether or not the original article was a "deconstruction," and whether Julia Kristeva can be assimilated satisfactorily to structural linguistics. More fundamentally, the response proposes that, despite his stated ambitions, Renwick, in fact, provides a deeply heterogeneous Schenker; and finally, that Renwick's claim for music theory's current practices rests on a conflation of productivity, as I describe it, with electicism.